The Samaritan "brought him to an inn": Revisiting πανδοχεῖον in Luke 10:34 - Eck, Ernest van (HTS teologiese studies, 2018)
This article traces the meaning of κατάλυμά and πανδοχεῖον in available Roman-Egypt papyri, the LXX, early-Jewish literature, and Greek writings to determine the meaning of πανδοχεῖον [inn] used in Luke 10:34. It is argued that a lexical study of κατάλυμά and πανδοχεῖον and available information on travel in the ancient world indicate that there is no evidence for the so-called non-commercial inns in the ancient world and that commercial inns and innkeepers, in principle, were all ‘bad’. In conclusion, the implications of this understanding of πανδοχεῖον and πανδοκεύς (Lk 10:34, 35) for the possible intended meaning of the parable are discussed, a conclusion that begs further research regarding the identity of the protagonist in the parable.